Harpagide, a natural product, promotes synaptic vesicle release as measured by nanoelectrode amperometry. Issue 3 (5th December 2019) - Tang, Yun; Yang, Xiao-Ke; Zhang, Xin-Wei; Wu, Wen-Tao; Zhang, Fu-Li; Jiang, Hong; Liu, Yan-Ling; Amatore, Christian; Huang, Wei-Hua
Abstract : Nanoelectrode amperometry was used to monitor DA release inside single DAergic synapses, and demonstrated that harpagide effectively enhances synaptic DA release by reducing intracellular ROS generation and inhibiting α-Syn phosphorylation. Abstract : Parkinson's disease (PD) is a neurodegenerative disorder characterized by progressive loss of dopaminergic (DAergic) neurons and low level of dopamine (DA) in the midbrain. Recent studies suggested that some natural products can protect neurons against injury, but their role on neurotransmitter release and the underlying mechanisms remained unknown. In this work, nanoelectrode electrochemistry was used for the first time to quantify DA release inside single DAergic synapses. Our results unambiguously demonstrated that harpagide, a natural product, effectively enhances synaptic DA release and restores DA release at normal levels from injured neurons in PD model. These important protective and curative effects are shown to result from the fact that harpagide efficiently inhibits the phosphorylation and aggregation of α-synuclein by alleviating the intracellular reactive oxygen level, being beneficial for vesicle loading and recycling. This establishes that harpagide offers promising avenues for preventive or therapeutic interventions against PD and other neurodegenerative disorders.